Improvement of soil fertility and weed suppression through legume-based technologies - Collaborative Group on Maize-Based Systems Research (1995)
Increasing populations in West and Central Africa leads to intensification of land use and reduced fallow periods. Agricultural intensification in turn, results in degradation of soil fertility, erosion, spread of diseases, pests and weeds. Leguminous plants, integrated into existing cropping systems, currently offer the best potential to overcome constraints. The Collaborative group on Maize-Based Systems Research (COMBS), through on-farm research, tries to match available technologies with a diversity of farming systems. This document is based on present experiences.